Transformation of Consumer Behavior Through Smart City Technology: A Literature Review - Febiyanti, Widyantari; Nadlifatin, Reny (Journal of Information System and Informatics, 2024)
Once city implements a smart city, the transformation that occurs not only impacts the city's infrastructure and operations, but also significantly influences individual interactions with public facilities and their consumption patterns. This literature review aims to identify changes in consumer behavior and daily activities after the implementation of smart city technology. The methodology used is PRISMA, with references published over the last decade. The research results show changes in various aspects, including mobility, energy efficiency, citizen engagement, environmental awareness, shopping experience, quality of life, education and information, business prospects, and response to the crisis. These findings show that smart city technology brings positive changes in the daily lives of city residents, which are influenced by the use of technology and the way it is implemented by the community. This research provides insight for policy makers and city managers to understand the broad impact of smart cities on community behavior.